Media literacy : thinking critically about advertising - Paxson, Peyton. 4 0 16; 5 (Portland, ME : Walch Education, 2009)
Contains over forty activities designed to help students in grades seven to twelve gain a better understanding of advertising while building critical thinking skills, covering the history of advertising, public consumption, advertising to males and females, television and radio advertising, print and outdoor advertising, and the new media.
Running title: Media literacy
Includes bibliographical references (p. 122).
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching (Middle school);Study and teaching (Middle school);Social aspects;Study and teaching (Middle school);Study and teaching (Secondary);Study and teaching (Secondary);Social aspects;Study and teaching (Secondary);Study and teaching.;Study and teaching.;Study and teaching. -- Media literacy;Advertising;Mass media;Media literacy;Advertising;Mass media;Media literacy;Advertising;Mass media -- Activity programs.;Activity programs.;Activity programs.;Activity programs.;Activity programs.;Activity programs; 20; 2